A Novel Homozygous CYP19A1 Gene Mutation: Aromatase Deficiency Mimicking Congenital Adrenal Hyperplasia in an Infant without Obvious Maternal Virilisation - Fatma Dursun; Serdar Ceylaner (Galenos Yayincilik, 2019)
Aromatase deficiency is a rare, autosomal recessive disorder in which affected patients fail to synthesize normal estrogen. Herein, we report a 46, XX patient born with virilised external genitalia. A novel homozygous mutation in the CYP19A1 gene, causing aromatase deficiency, was detected. A 30-day infant registered as a male was referred to pediatric endocrinology because of a uterus detected on ultrasonography. The infant was born at 23 gestational weeks by C-section because of preeclampsia and premature membrane rupture. The parents were consanginenous. There was no evidence of virilisation, such as acne, hirsutism, deep voice or clitoral enlargement in the maternal history. Physical examination of the infant revealed complete scrotal fusion and a single urogenital meatus, consistent with Prader stage-3. A standard dose adrenocorticotropic hormone (ACTH) test revealed an inadequate cortisol response and high 17-hydroxy progesterone levels, suggesting simple virilising congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency. However, no mutation in the CYP21A2 gene was detected. At age 2.5 years the ACTH test was repeated, after suspension of hydrocortisone treatment for 48 hours, when resulting cortisol and androgen levels were normal. The patient was re-evaluated in terms of 46, XX disorders of sex development (DSD), especially with a suspicion of aromatase deficiency. A novel, homozygous, exon 6 deletion was identified in the CYP19A1 gene. Aromatase deficiency may be confused with CAH in the newborn period. In this case 46, XX DSD aromatase deficiency was present in the absence of a history of maternal virilisation or large and multicystic ovaries.